Investigating the Effect of Hearing Aid Use on the Balance Status of Children with Severe to Profound Congenital Hearing Loss Using the Pediatric Clinical Test of Sensory Interaction for Balance - Hamzehpour, Farzad; Absalan, Aghil; Pirasteh, Ebrahim; Sharafi, Zahra; Arbabsarjoo, Hamideh (Journal of the American Academy of Audiology, 2021)
Background Since the hearing and vestibular organs are close to each other, the correlation between hearing and balance is one of the principal issues, especially in people with hearing loss.Purpose In this study, the effect of the auditory system on human balance performance was investigated by comparing the balance status of hearing-impaired children in the aided and unaided situations.Research Design In this cross-sectional study a group of children were assigned the task to compare the balance sways in two aided and unaided situations.Study Sampling A total of 90 children aged 7 to 10 years with severe to profound congenital hearing loss and the healthy vestibular system of both genders served as the research population.Data Collection and Analysis After a complete evaluation of the hearing and vestibular system and validation of the hearing aid performance, body sway was recorded using the pediatric clinical test of sensory interaction for balance in aided and unaided situations in the presence of background noise from the speaker.Results According to this study, there was no difference in body sway in aided and unaided situations for conditions 1, 2, and 3. In comparison, in conditions 4, 5, and 6 of the test, there was a statistically significant difference in body sway between aided and unaided situations. However, there was no difference in the sway of the body in aided and unaided situations between girls and boys.Conclusion According to this study, hearing aids can improve balance in challenging listening environments.
Keywords: hearing loss; sensory interaction; balance